Female participation in Agroecology: Sustainable development and the search for gender equality - Brandão, Gabriella Henrique; Souza, Bruna dos Santos; Barroso, Vitória Saskia Ferreira; Silva, Luana Rêgo; Lima, Deise Maria Farias (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2019)
The Development of Sustainable and the fight for equality between genders are themes directly linked, once the agricultural women are responsible for promoting hair environmental conservation, utilization of natural invasive control practice biofertilizer production, planting of various vegetables and various medical plants, contributing to biodiversity diversity, help to keep alive the culture of Creoles, assuming in this interim posture of environmental and cultivation preservation. A qualitative investigation was carried out not a Trade Union of Remígio-PB Rural Workers, aiming to know the perceptions about female labor relations in agriculture and to value the knowledge of female farmers, relating them to sustainable development and the importance of the struggle for equality in relations between genders. Given this can be affirmed that the Sustainable Development depends on autonomy this can be achieved through equal opportunities and relationships between men and women.